The Labor Market Effects of Immigration Enforcement - Chloe N. East; Philip Luck; Hani Mansour; Andrea Velasquez (Institute of Labor Economics (IZA), 2018)
This paper examines the effects of reducing the supply of low-skilled immigrant workers on the labor market outcomes of domestic workers. We use temporal and geographic variation in the introduction of Secure Communities (SC), a county-based immigration enforcement policy, combined with data over 2005-2014 from the American Community Survey to estimate a difference-in-difference model with geographic and time fixed effects. We find evidence that SC had a negative impact on the employment of low-skilled non-citizen workers, who are likely to be directly affected by the policy. Importantly, we also find that SC negatively impacted the employment of citizens working in middle to high-skill occupations. This is the first paper to provide quasi-experimental evidence on the labor market effects of immigration enforcement policies on citizens across the occupational skill distribution, which is of paramount importance given the current immigration policy debates.
Keywords: F22; J11; J23; K37; 330; labor demand; international migration; immigration policy